Labour supply of households facing a risk of job loss - Wouter Gelade; Maud Nautet; Céline Piton (National Bank of Belgium, 2022)
The impact of a job loss on partner's labour supply - often called the added worker effect - is a well-studied phenomenon. However, people might already adjust their labour supply when their partner is at risk of losing his/her job. Using Labour Force Survey (LFS) microdata, we quantify this effect for 16 European countries over the period 2005-2020. When a household member is at risk of losing his/her job, the partner is 30% more likely to enter the labour market (extensive margin) and 52% more likely to (want to) increase working hours (intensive margin). These effects are almost as big as those of an actual job loss for the intensive margin, and a bit more than half of those for the extensive margin. Fear of job loss is thus an important additional factor influencing households' labour supply. This is particularly true in periods of crisis, in which the effects of fear of job loss and actual job loss are equally big. Heterogeneity analysis shows that different households adjust their labour supply at different moments, with low-educated people already adjusting when fearing job loss, while the high-educated wait for this risk to materialise.
Keywords: J22; D13; 330; Labour supply; household decisions; risk; added worker effect